The effect of freeze-thaw cycles on phosphorus release from riparian macrophytes in cold regions. Issue 2 (3rd April 2019) - Whitfield, Colin J.; Casson, Nora J.; North, Rebecca L.; Venkiteswaran, Jason J.; Ahmed, Osama; Leathers, Jeremy; Nugent, Katy J.; Prentice, Tyler; Baulch, Helen M.
Abstract: Storage and removal of nutrients by wetlands and riparian areas is an important process in understanding catchment nutrient fluxes and in helping to mitigate current issues of eutrophication in many regions. In cold climates, strong seasonality affects natural wetlands and those constructed for water treatment alike, raising important questions about how ecosystems can be managed to maximize nutrient retention in the landscape, particularly in light of rapid and ongoing wetland loss. This study assessed how freeze-thaw cycles (FTCs) affect the release of phosphorus (P) from common riparian macrophytes ( Typha spp). The goal was to understand whether the freeze-thaw processes could drive enhanced nutrient release as has been shown for agricultural residues, but which has not previously been assessed in riparian vegetation. Given the rapid expansion of Phragmites australis in parts of the study area, this study also tested the effects of FTC on P release from Phragmites tissue. A common experimental protocol was used across 11 wetlands in three regions of Canada. These results demonstrate the potential for FTCs to induce P release from macrophyte tissue, although this is not observed in all cases. The impact of FTCs on P release was greatest and most consistent when samples were collected earlier in the growing season. Release rates were positively correlated with plant P content. This suggests that the degree of plant senescence may play a role in determining the response to FTCs. Typha and Phragmites showed similar responses to FTCs, suggesting that the importance of this process does not depend on the dominant taxon. Sequential FTCs led to further enhancement of P release from macrophyte tissue. The results from this study suggest that specific management such as harvesting Typha during the growing season, may mitigate the potential for P release due to FTCs.